2006
DOI: 10.1016/j.rmedu.2006.01.015
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein in patients with COPD, control smokers and non-smokers

Abstract: Background: Patients with chronic obstructive pulmonary disease (COPD) have raised serum levels of C reactive protein (CRP). This may be related directly to COPD and its associated systemic inflammation or secondary to other factors such as concomitant ischaemic heart disease (IHD) or smoking status. The aim of this study was to evaluate IHD and smoking as potential causes of raised CRP levels in COPD and to test the association between inhaled corticosteroid (ICS) use and serum CRP levels. Methods: Cross sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
117
4
15

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(155 citation statements)
references
References 9 publications
19
117
4
15
Order By: Relevance
“…23 Therefore, comparisons of our results with the literature are limited, as other studies used patients with more severe COPD. [24][25][26][27] The values of the oxidative stress markers from the severe and very severe groups in our study were always higher than those of the patients with mild or moderate COPD, which is in keeping with what has been published. 28 Studies assessing other oxidative stress markers, such as 4-hydroxy-2-nonenal (4-HNE) in airways and alveolar epithelial cells, 28 and an analysis of condensed air 25 also found a negative correlation between these markers and the severity of the disease assessed through FEV 1 as we found in our study (r ¼ -0.39; p ¼ 0.01; Figure 1).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…23 Therefore, comparisons of our results with the literature are limited, as other studies used patients with more severe COPD. [24][25][26][27] The values of the oxidative stress markers from the severe and very severe groups in our study were always higher than those of the patients with mild or moderate COPD, which is in keeping with what has been published. 28 Studies assessing other oxidative stress markers, such as 4-hydroxy-2-nonenal (4-HNE) in airways and alveolar epithelial cells, 28 and an analysis of condensed air 25 also found a negative correlation between these markers and the severity of the disease assessed through FEV 1 as we found in our study (r ¼ -0.39; p ¼ 0.01; Figure 1).…”
Section: Discussionsupporting
confidence: 91%
“…The negative correlation between CRP and the distance walked during the 6MWT found by us is similar to the findings of Pinto-Plata et al 27 and Torres et al 24 The fact that the correlation was stronger between CRP and the BODE index than a multidimensional index that does not take into account the 6MWT 10 seems to demonstrate that CRP is actually well associated with physical capacity. It was recently shown that physical activity reduces the risk of having high levels of circulating TNF-a and CRP.…”
Section: Discussionsupporting
confidence: 90%
“…They also showed a linear association of CRP with the number of cigarettes smoked per day [29]. A study by PintoPlata et al also supported our study [30].…”
Section: Discussionsupporting
confidence: 91%
“…However, another study conducted in people of Japanese ethnicity (the Iwate Kenpoku Cohort study) failed to identify any significant relationship between serum CRP concentration and the number of cigarettes smoked per day (31) . MONICA study from Germany, reported significantly high serum CRP concentrations in male smokers with no significant difference in women smokers 32 . In contrast, another study examining CRP levels in patients with moderate to severe COPD reported that, although there was a significant difference in CRP levels in the COPD patients, there was no difference in CRP status between smokers and non-smokers 33 .…”
Section: Discussionmentioning
confidence: 96%